On migration, geography, and epistemic communities - Russell King (Comparative Migration Studies, 2020)
Abstract This commentary paper starts by questioning the assumption that migration means international migration, and goes on to affirm that migration studies has indeed come of age as a coherent if highly diverse research field. Several emerging epistemic communities are identified: migration and development; gender and migration; lifestyle migration; and youth and student migrations. Finally, I argue that the role of geography in the study of migration has been under-valued.